Toxoplasmosis in Females from Al-Anbar, Iraq. - AlKubaisi, Salaah Aldeen M.; Al-Zubaidy, Ibrahim A. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Toxoplasmosis is a common zoonotic disease affecting one-third of the world population with potentially serious health implications. Objectives: To find the prevalence and risk factors of Toxoplasma gondii infection among females in Al-Anbar, Iraq. Methods: Over an eight-month period from (1st November 2021 to 30th June 2022), 200 females visiting private veterinary clinics in Al-Anbar (92 owned cats) participated in this prospective study. Age and residency were recorded. Blood samples were collected from all females and subjected first to the Toxoplasma Latex Agglutination test (TLAT). Samples of cat feces were collected from 57 (62%) pet and 35 (38%) stray cats and subjected first to direct microscopy looking for Toxoplasma oocysts. Blood and fecal samples were then tested by nested polymerase chain reaction (n-PCR) and real-time PCR. Results were then statistically analyzed. Results: Rates of human toxoplasmosis were (n=48, 24%), (n=60, 30%), and (n=77, 38.5%) with TLAT, n-PCR, and RT-PCR tests respectively. Likewise, rates of cat toxoplasmosis were (n=7, 7.6%), (n=55, 60%), and (n=80, 87.0%) with TLAT, n-PCR, and RT-PCR tests respectively. Results of the latex test revealed that females >40 had a high rate of infection (45.8%) compared with those aged 31-40 years (33.8%) and those aged 21-30 years (13.0%) (P≤0.01). City resident females had a lower infection rate compared to village residents (29.7% vs. 55.4%). Conclusions: Toxoplasmosis was more prevalent in females >40 from rural areas but wasn’t related to contact with cats. Real-time PCR provided a better diagnostic yield.